2014
DOI: 10.7314/apjcp.2014.15.6.2541
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and Therapy of Primary Hepatic Neuroendocrine Carcinoma: Clinical Analysis of 10 Cases

Abstract: Background: Primary hepatic neuroendocrine carcinoma (PHNEC) is rarer than extrahepatic gastrointestinal neuroendocrine carcinoma (NEC). It is difficult to make a correct diagnosis and poses a challenge for management. Materials and Methods: Ten PHNEC patients were admitted to our hospital from June 2006 to June 2011. Laboratory tests and imaging scans were performed for diagnosis and exclusion of extrahepatic NEC. All patients were AFP -and CA199-. Seven patients had solid tumors with cystic changes on ultras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 22 publications
0
27
0
Order By: Relevance
“…Currently, surgery is the only curative option and provides the most favorable outcome, including long-term survival [ 15 ]. Only 33 reports of surgery in PHNEC patients have been published in the literature (Table 1 ) [ 2 , 4 , 7 , 10 , 11 , 13 – 15 , 19 , 20 , 22 24 , 26 ]. Park et al reported on three patients with resectable tumors who were alive 17.7 months after treatment (range, 15.2–36.9 months) and on nine patients whose tumors could not be surgically removed but who survived for 11.3 months (range, 0.7–41.7 months) [ 20 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 4 more Smart Citations
“…Currently, surgery is the only curative option and provides the most favorable outcome, including long-term survival [ 15 ]. Only 33 reports of surgery in PHNEC patients have been published in the literature (Table 1 ) [ 2 , 4 , 7 , 10 , 11 , 13 – 15 , 19 , 20 , 22 24 , 26 ]. Park et al reported on three patients with resectable tumors who were alive 17.7 months after treatment (range, 15.2–36.9 months) and on nine patients whose tumors could not be surgically removed but who survived for 11.3 months (range, 0.7–41.7 months) [ 20 ].…”
Section: Case Presentationmentioning
confidence: 99%
“…It is a reason why adjuvant chemotherapy after curative resection should be considered, although no prospective studies are available to support this practice. While resection of all tumors could lead to a higher survival rate and better outcomes, many patients will still require combined therapy, such as transcatheter arterial chemoembolization, chemotherapy, and radiofrequency ablation [ 26 ].…”
Section: Case Presentationmentioning
confidence: 99%
See 3 more Smart Citations